Multi-arm azobenzene liquid crystal based on cholic acid: synthesis and mesophase properties. Issue 12 (26th September 2018) - Wang, Duo; Huang, Yu; Lv, Jin-Ming; Min, Yue; Quan, Yuan-Yuan; Ge, Li-Na; Tian, Mei; Yao, Dan-Shu
ABSTRACT: A new series of multi-arm liquid crystals (D1–D5 ) based on cholic acid as the chiral core and ω-[4-( p -substituted azobenzeneoxy carbonyl]valeric acid (B1–B5 ) as the mesogenic arms were designed and synthesised. All the mesogenic arms and the multi-arm liquid crystals were structurally well-characterised using elementary analysis (EA), 1 H NMR and FT-IR. The photochemical properties were determined by UV spectra. The optical rotations were measured by Automatic Polarimeter. The phase behaviours were investigated by means of polarised optical microscopy, X-ray diffraction and differential scanning calorimetry, while the effect of the terminal groups of azobenzene on mesogenic and photochemical properties were discussed. The results demonstrated that the mesogenic arms exhibited nematic phase exceptB3 . The multi-arm compounds showed chiral nematic exceptD3 . Cholic acid played an important role in inducing chiral nematic of the multi-arm liquid crystals. T m or T i ofB1 –B5 andD1 –D5 are influenced by the effect of electrical effects of the terminal groups and the molecular shapes. Furthermore, the multi-arm compounds exhibited well light sensitivity, owning the photoisomerisation of the tran -form azobenzene to the cis -form azobenzene. λ max ofD1 –D5 displayed blue shift first and then red shift with the different electrical effects of the terminal groups of mesogenic arms. GRAPHICAL ABSTRACT: